Response of Lipoprotein a, Blood Coagulation and Fibrinolysis Factors to Aerobic Exercise in Overweight Women - Roghayeh Shad; Nahid Bijeh; Mehrdad Fathi (Tehran University of Medical Sciences, 2019)
Background and Aim: Despite the significant progress in the field of health, Cardiovascular diseases are the leading cause of death among people. For this purpose, the present study was conducted to evaluate the effect of eight weeks of aerobic exercise on lipoprotein a, blood coagulation and fibrinolysis factors in overweight women. Materials and Methods: In this semi experimental study with pre and post-test design, 21 overweight women subjects aged between 20 and 30 were randomly selected from experimental (10 people) and control (11 people). The aerobic exercise protocol consisted of five sessions per week for 30 minutes and with an intensity of 55%-75% heart rate reserve (HRR). Blood samples were collected from subjects in two stages to evaluate the considered variables. Measurement of levels of Lipoprotein a, Fibrinogen, PT, PTT, Platelet counts and Hemoglobin. For data analysis, repeated measures of variance analysis at a significant level of 5 hundredths were used by employing SPSS software. Results: The mean values of Lipoprotein a, Fibrinogen, PT and Platelet counts in the control group showed no significant change after eight weeks of training (P>0.05). While PTT changes in the both groups was significant in the post-test compared to the pre-test (P=0.006). The inter-group difference, in any of the variables between the experimental and control groups, was not significant (P>0.05). Conclusion: Eight weeks of aerobic training had no effect on Lipoprotein a and blood coagulation and fibrinolysis factors, however, this training program can take effective steps in improving health promotion in overweight women.